Water in the GATS Methodology and Results - Miroudot, Sébastien (OECD Trade Policy Papers, 2015)
The water in the General Agreement on Trade in Services (GATS) refers to the difference between the bound level of trade restrictiveness permitted by the GATS and the actual trade regime. Using the OECD Services Trade Restrictiveness Index (STRI), this report provides estimates of the water in 15 service sectors for 40 countries. The level of water in GATS commitments varies across sectors. It is highest in sectors where most countries have no commitments (unbound), such as audio-visual services or transport services, as well as sectors where countries tend to make commitments only for selected types of activities, such as legal services. The lowest level of water is observed in sectors such as telecoms, construction, computer and distribution services that are also characterised by a more liberal trade regime. Generally speaking, current services trade policies are much more open than what countries have committed in the GATS and sectors that are "unbound" can be fairly open